PERAN BMT DALAM MENGATASI KEMISKINAN DI KABUPATEN BANTUL - Jaka Sriyana; Fitri Raya (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2013)
This study aims to analyze the role of BMT in reducing poverty in Bantul, especially from the aspect of BMT role in increasing income members. This research applies regression analysis with data perception of the BMT’s members. The results show that business education variable, the Baitul Maal funds utilization, and motivation to work the members have a significant role in increasing the income of the members. Baitul Maal fund utilization significantly affects to increase their income. Motivation factor is also one of the variables that affect their income. From these results may be taken to imply that the perception of members of the existence and role of BMT to increase people’s income in order to decrease the poverty was primarily due to activities that are social, educational, and increased motivation to work.